Immunisation status of children under 2 years of age visiting Khyber Teaching Hospital, Peshawar, Pakistan: a cross-sectional analysis - Muhammad Khan; Jehan Hussan; Laiba Gul; Mehran Ali; Afroz Ali; Nimra Khattak; Laiba Ali; Abida Ambreen; Muhammad Baryal Khan; Cyrus Wasim; Rafi Ullah (BMJ Open)
Objective The study was conducted to determine the immunisation status of children under 2 years of age, assess the determinants of non-immunisation and evaluate the association between immunisation status and various sociodemographic factors.Methods A cross-sectional questionnaire-based study was conducted at the outpatient department of Khyber Teaching Hospital, Peshawar, over a period of 4 months. A convenience sampling technique was used and the sample size was calculated using the WHO sample size formula, resulting in n=363. A semistructured questionnaire was used to measure the primary outcome, which was the immunisation status of children under 2 years of age. Immunisation data were verified through vaccination cards to ensure accuracy and minimise recall bias. The questionnaire also collected information on sociodemographic factors, including maternal education, place of residence and household income. Statistical analysis was done at the end of the study using SPSS (V.25).Results According to the vaccination card, it was found that 43.3% of the children were fully immunised, 32.5% of the children were partially immunised and the percentage of unimmunised children was 24.2.Conclusion We found that the immunisation status of children was not satisfactory. Sustained efforts are required to achieve universal coverage of immunisation. Significant interventions are required, especially in areas that are more rural and less educated.